2021
DOI: 10.1080/14616688.2021.1916584
|View full text |Cite
|
Sign up to set email alerts
|

(Post-) pandemic tourism resiliency: Southeast Asian lives and livelihoods in limbo

Abstract: b Bournemouth university, poole, uK; c university of hawai'i at mānoa, honolulu, usa; d hospitality and Tourism institute, Faculty of social sciences and humanities, Duy Tan university, Danang, Viet Nam

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Research on resilience in tourism studies has predominantly focused on economic resilience, shortterm disasters and hazards, highly vulnerable systems, and long-term climate change impacts (Adams et al, 2021;Bec et al, 2015;Coaffee & Wood, 2006;Dogru et al, 2019;Hamzah & Hampton, 2013;Larsen et al, 2011;Lew, 2014). Historically, the foundation of the resilience conceptual framework in tourism studies can also be identified in the theories proposed by Holling (1973), which focuses on ecological system context, and Adger (2000), who has used a resilience approach to analyze the complexity of social phenomena related to the environment.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Research on resilience in tourism studies has predominantly focused on economic resilience, shortterm disasters and hazards, highly vulnerable systems, and long-term climate change impacts (Adams et al, 2021;Bec et al, 2015;Coaffee & Wood, 2006;Dogru et al, 2019;Hamzah & Hampton, 2013;Larsen et al, 2011;Lew, 2014). Historically, the foundation of the resilience conceptual framework in tourism studies can also be identified in the theories proposed by Holling (1973), which focuses on ecological system context, and Adger (2000), who has used a resilience approach to analyze the complexity of social phenomena related to the environment.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Historically, the foundation of the resilience conceptual framework in tourism studies can also be identified in the theories proposed by Holling (1973), which focuses on ecological system context, and Adger (2000), who has used a resilience approach to analyze the complexity of social phenomena related to the environment. Resilience, in general, can be defined as the ability of a particular object or system to return to its original posture by absorbing disturbance and reorganizing while undergoing change in an effort to accomplish post-disaster balance by retaining essentially the same function, structure, identity, and feedback (Adams et al, 2021;Davoudi et al, 2012;Holling, 1973;Walker et al, 2004).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Lacking the requisite set of land use permits due to bureaucratic delays, informal tenurial arrangements or landlessness, villagers in many areas have been compelled to exploit resource extraction opportunities presented by reduced environmental monitoring amidst border restrictions. Across Southeast Asia, there have been reports of intensified artisanal gold panning ( Straits Times, 2020 ), sand mining ( ASEAN, 2020 ) and illegal logging, including in national parks that have lost ecotourism revenues ( Adams et al, 2021 ) and reduced ranger patrols during pandemic lockdowns ( Cahyadi & Newsome, 2021 ).…”
Section: Introductionmentioning
confidence: 99%